Flexure Behaviour of Foamed Concrete Incorporating Banana Skin Powder and Palm Oil Fuel Ash Strengthened with Carbon Fibre Reinforced Plate. (August 2019) - Mohamad, Noridah; Afif Iman, Muhammad; Aziz Abdul Samad, Abdul; Othuman Mydin, Md Azree; Jusoh, Suriani; Sofia, Anis; Aziz, Khalidah; Lee, Bryan
Abstract: This paper investigated the chemical properties of banana skin powder (BSP) and palm oil fuel ash (POFA), and mechanical properties of lightweight foamed concrete (LFC) incorporating BSP and POFA strengthened with carbon fibre reinforce polymer (CFRP) plate. The BSP and POFA are added in the LFC mixture at various percentages as cement and sand replacement, respectively. LFC cubes incorporating BSP and POFA, LFC-BSP-POFA, were cast and tested under compression to determine its compressive strength. LFC-BSP-POFA prisms strengthened with 100 mm and 150 mm length of CFRP plates glued on its bottom mid-span surface were cast and tested under four point bending load to determine its flexure behaviour. From the chemical test, it was found that BSP and POFA each contain pozzolan materials, which are 55.98% and 51.83% silicon dioxide, and 2.71% and 2.32% aluminium oxide, respectively. From the mechanical property tests, compressive and flexural strength increased when percentage of BSP and POFA incorporated in the LFC increased. Meanwhile, CFRP plate managed to strengthen the LFC prism further where higher ultimate load recorded when longer CFRP plate was used.